PENGARUH ROTASI KERJA, PENGAWASAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANFAAT GROUP KABUPATEN SEMARANG (Studi Kasus pada Karyawan Pabrik Bagian Produksi Tepung) - Emi Nursanti; Naili Farida; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
The research was motivated by the complaints of the employees about job rotation in Manfaat Group Company Kabupaten Semarang. In addition, in the last one year, there was increasing of product reject quality control, another case about decreasing of company performance in last thee years. The aim of this research is conducted to determine the influence of job rotation, job supervision and compensation to company performance through motivation in Manfaat Group Company Kabupaten Semarang.The population is all of employees of flour production division with 102 samples. The analysis used in this research is the Partial Least Square (PLS) using software SmartPLS 2.0 M3 for Windows, which previously tested the validity and reliability first.Based on calculations show that variable job rotation have an influence to motivation, variable job supervision have an influence to motivation, variable compensation have an influence to motivation, variable motivation have an influence to job performance, variable job rotation have an influence to job performance and variable compensation have an influence to job performance.